Mass spectrometric insights into the protein composition of human cutaneous neurofibromas: comparison of neurofibromas with the overlying skin. - Kallionpää, Roope A.; Martikkala, Eija; Haapaniemi, Pekka; Karppinen, Sanna-Maria; Riihilä, Pilvi; Rokka, Anne; Leivo, Ilmo; Pihlajaniemi, Taina; Peltonen, Sirkku; Peltonen, Juha (SPRINGER NATURE, 2025)
Background: Cutaneous neurofibromas (cNFs) are the hallmark of the tumor-predisposition syndrome neurofibromatosis 1 (NF1). While cNFs are always benign, they markedly decrease quality of life in individuals with NF1. Understanding the differences between cNFs and the skin is essential for developing treatments for cNFs.
Methods: We collected 15 cNFs from four NF1 individuals and used mass spectrometry to compare the tumor tissue with the skin overlying each tumor. Data were analyzed based on Gene Ontology (GO) terms.
Results: The expression patterns of the Schwann cell marker S100B and several keratins confirmed successful dissection of cNF tissue from the overlying skin. Hierarchical clustering showed extensive overlap between the tumor and skin samples in three out of four individuals, suggesting high overall similarity between the two tissue types. Based on the analysis of the GO terms, cNFs were associated with decreased expression of proteins related to cell proliferation, extracellular matrix remodeling, angiogenesis and cellular metabolism.
Conclusion: The cNFs are relatively quiescent, consistent with their benign nature and limited growth potential. The development of pharmacological therapy for cNFs requires overcoming the high similarity between cNFs and the overlying skin. The present dataset can serve as a resource for future research on cNFs.